Incremento en el peso de ninfas y adultos de Podisus nigrispinus (Heteroptera: Pentatomidae) alimentados con dos tipos de larva - Zanuncio, José C (1996)
The daily weigth increment of Podisus nigrispinus (Dalias, 185 1) (Heteroptera: Pentatomidae) during 42 and s.º instars and the adult stage was studied at 25±O.50C, 60±1O% relative humidity and photophase of 12 h. Dai1y variations of weigth, after regression analysis, were highly significant for males and females during both instars when fed Musca domestica Linnaeus, 1 758 (Diptera: Muscidae) and Tenebrio molitor Linnaeus, 1758 (Coleoptera: Tenebrionidae) larvae. A higher weight increase of P. nigrispinus was recorded during the first 24 hours of feeding. No weight increase was found for males but the females increased in weight after four days of age, reflecting reproductive tissue growth.